Lymphocyte‐independent pathways underlie the pathogenesis of murine cytomegalovirus‐associated secondary haemophagocytic lymphohistiocytosis. (18th January 2018) - Brisse, E.; Imbrechts, M.; Mitera, T.; Vandenhaute, J.; Berghmans, N.; Boon, L.; Wouters, C.; Snoeck, R.; Andrei, G.; Matthys, P.
Summary: Haemophagocytic lymphohistiocytosis (HLH) constitutes a spectrum of immunological disorders characterized by uncontrolled immune activation and key symptoms such as fever, splenomegaly, pancytopenia, haemophagocytosis, hyperferritinaemia and hepatitis. In genetic or primary HLH, hyperactivated CD8 + T cells are the main drivers of pathology. However, in acquired secondary HLH, the role of lymphocytes remains vague. In the present study the involvement of lymphocytes in the pathogenesis of a cytomegalovirus‐induced model of secondary HLH was explored. We have previously reported CD8 + T cells to be redundant in this model, and therefore focused on CD4 + helper and regulatory T cells. CD4 + T cells were activated markedly and skewed towards a proinflammatory T helper type 1 transcription profile in mice displaying a severe and complete HLH phenotype. Counter to expectations, regulatory T cells were not reduced in numbers and were, in fact, more activated. Therapeutic strategies targeting CD25 high hyperactivated T cells were ineffective to alleviate disease, indicating that T cell hyperactivation is not a pathogenic factor in cytomegalovirus‐induced murine HLH. Moreover, even though T cells were essential in controlling viral proliferation, CD4 + T cells, in addition to CD8 + T cells, were dispensable in the development of the HLH‐like syndrome. In fact, no T or B cells were required for induction and propagation of HLH disease, as evidenced by the occurrence of cytomegalovirus‐associated HLH in severe combined immunodeficient (SCID) mice. These data suggest that lymphocyte‐independent mechanisms can underlie virus‐associated secondary HLH, accentuating a clear distinction with primary HLH. Abstract : In the present study the involvement of lymphocytes in the pathogenesis of a cytomegalovirus‐induced model of secondary HLH was explored. Even though T cells were essential in controlling viral proliferation, CD4+ T cells, in addition to CD8+ T cells, were dispensable in the development of the HLH‐like syndrome. In fact, no T or B cells were required for induction and propagation of HLH disease, suggesting that lymphocyte‐independent mechanisms can underlie virus‐associated secondary HLH.